THE EFFECT OF THE VILLAGE LITERACY MOVEMENT PROGRAM ON INCREASING READING INTEREST AND COMMUNITY PRODUCTIVITY IN KALIMANGGIS KULON VILLAGE - Reizal Zahara Rizki; Euis Nurohmah; Shifa Defina Putri; Sania Aizatul Ma'wa; Desi Maelinda; Sihol Marito br Siagian; Vika Nabilla Amwa; Muhammad Gilang Ramadhan (Ann Publisher, 2026)
Abstract Background. By expanding access to literacy facilities, outreach, and literacy training, the literacy movement seeks to improve literacy culture at the local level and encourage the reading enthusiasm and productivity. Aims. Literacy of the residents of Kalimanggis Kulon Village. Governments, educational institutions, communities, and the general public are involved in these efforts. Methods. Through the Participatory Action Research (PAR) approach, namely the PAR method, this study uses a descriptive qualitative methodology. Result. Public knowledge of literacy, the availability of high-quality books and reading materials, and reading culture have increased significantly as a result of the implementation of this literacy movement. Conclusion. Although literacy groups at the village level have improved social cohesion and community empowerment, literacy outreach and training have effectively inspired adults and children to read more. Implementation. Improving people's social and economic capabilities makes it easier for them to access information and job opportunities, which is another significant benefit. Keywords: Programs, Literacy Movement, Society and Reading Interest